Effect of La doping in transparent 0.67Pb(Mg1/3Nb2/3)O3–0.33PbTiO3 ceramics fabricated by conventional sintering. Issue 19 (14th October 2014) - Fujii, Ichiro; Ono, Hiroyuki; Wada, Takahiro
Abstract: Abstract : Transparent 0.67(Pb1− x La x )(Mg1/3 Nb2/3 )O3 –0.33(Pb1− x La x )TiO3 ( x = 0–0.05) ceramics were successfully prepared without using a hot-pressing technique. The optical transmittance at the wave length of 400–2000 nm increased with increasing lanthanum (La) content, x from 0 to 0.03. The transmittance at 600–2000 nm further increased (with the highest transmittance of 68% at 2000 nm for ceramics with thickness of 0.5 mm) at x = 0.04 and 0.05, while the transmittance at 400–600 nm decreased. X-ray diffraction patterns suggested that the overall increase in the transmittance with x was associated with a change in the crystal systems from a monoclinic phase to a pseudocubic phase, and the decrease at x = 0.04 and 0.05 was related to the formation of an impurity second phase. Their microstructures and dielectric properties were also studied.